EVALUASI SHAPE FACTOR DALAM MEMBERI ANGKA KEAMANAN PADA KONSEP ELASTIS BAJA - Ningrum, Diana (SISTEM Jurnal Ilmu Ilmu Teknik, 2016)
Up to now we’ve known that there are two concepts in steel construction design: elastic method and plastic method. These both methods are based on the behavior of steel, obtained from stress-strain curve in a simple tension or compression test, elastic behavior, plastic, strain hardening and the process of fracture behavior. Elastic method is based on elastic behavior which means that the change stress and strain are proportional up to the accurance of the primary yield stress. In actual elastic design method the primary yield stress value is not used at all, but its less value is obtained by giving a number of safety factor and this stress called allowable stress. This safety factor value then becomes the bisure of safety in elastic design method. Because of the ductility behavior of steel, its real strength is higher than what is predicted in elastic method. In this section where the moment maximum occurs the moment could be developed till the section undergoes fully plastic (all of the section’s fibers are yield). One course of the advantage value of strength is buy a kind of cross section structure’s component called shape factor (SF) as a hidden safety factor in elastic design method. By knowing the shape factor value of each structure’s component section, it will give a direction to sort the section of structure’s component which has the less shape factor value, therefore there is no dissipation of material in design because a higher safety factor means more dissipation. The analysis proved that the structure’s component which has I shape section has the less shape factor value average 1,12. It means the number of safety factor that is not included in calculation is only 12%, so it is the most efficient section for structure’s component.